2002
DOI: 10.1021/jo011032n
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalyzed [2 + 2 + 2]-Cycloaddition of Nitriles with Acetylene:  An Effective Method for the Synthesis of 2-Pyridines under Mild Conditions

Abstract: The photocatalyzed [2 + 2 + 2]-cycloaddition of nitriles with 2 equiv of acetylene to 2-pyridines can be carried out under mild conditions and represents a valuable extension to common synthetical methods. For the ideal wavelength range (350-500 nm), lamps as well as sunlight can be used. Working at room temperature and in organic solvents such as toluene or hexane as well as in water gives satisfying results in many cases. However, it is also possible to vary the solvent and the reaction temperature of the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(49 citation statements)
references
References 21 publications
1
48
0
Order By: Relevance
“…An acetyl-substituted Cp ligand led to a faster conversion than an unsubstituted Cp ligand, while the indenyl ligand proved to have the slowest conversion rate, which is in accordance to the reports by Bönnemann and colleagues (Bönnemann et al 1984, Heller et al 2002.…”
Section: Complexes With Two Identical Neutral Ligands Olefinssupporting
confidence: 91%
“…An acetyl-substituted Cp ligand led to a faster conversion than an unsubstituted Cp ligand, while the indenyl ligand proved to have the slowest conversion rate, which is in accordance to the reports by Bönnemann and colleagues (Bönnemann et al 1984, Heller et al 2002.…”
Section: Complexes With Two Identical Neutral Ligands Olefinssupporting
confidence: 91%
“…It has been shown that the reaction was chemospecific and several different functional groups were well incorporated in this transformation without being protected, such as alcohols, ketones, and amines. [154] Additionally, photocatalyzed [2 + 2 + 2] alkyne or alkyne-nitrile cyclotrimerization in water [155][156][157] and cyclotrimerization in supercritical H 2 O [158,159] have been reported in recent years.…”
Section: Hetero-[2 + 2 + 2] Cyclotrimerizationmentioning
confidence: 99%
“…[19] These cycloadditions possessed an expanded substrate scope as terminal diynes were successfully converted into pyridine products. [19] These cycloadditions possessed an expanded substrate scope as terminal diynes were successfully converted into pyridine products.…”
Section: Methodsmentioning
confidence: 99%